Microspore embryogenesis: targeting the determinant factors of stress-induced cell reprogramming for crop improvement - Testillano, P. S.
Under stress, isolated microspores are reprogrammed in vitro towards embryogenesis, producing doubled haploid plants that are useful biotechnological tools in plant breeding as a source of new genetic variability, fixed in homozygous plants in only one generation. Stress-induced cell death and low rates of cell reprogramming are major factors that reduce yield. Knowledge gained in recent years has revealed that initiation and progression of microspore embryogenesis involve a complex network of factors, whose roles are not yet well understood. Here, I review recent findings on the determinant factors underlying stress-induced microspore embryogenesis, focusing on the role of autophagy, cell death, auxin, chromatin modifications, and the cell wall. Autophagy and cell death proteases are crucial players in the response to stress, while cell reprogramming and acquisition of totipotency are regulated by hormonal and epigenetic mechanisms. Auxin biosynthesis, transport, and action are required for microspore embryogenesis. Initial stages involve DNA hypomethylation, H3K9 demethylation, and H3/H4 acetylation. Cell wall remodelling, with pectin de-methylesterification and arabinogalactan protein expression, is necessary for embryo development. Recent reports show that treatments with small modulators of autophagy, proteases, and epigenetic marks reduce cell death and enhance embryogenesis initiation in several crops, opening up new possibilities for improving in vitro embryo production in breeding programmes.
Keywords: AUTOPHAGY; CELL DEATH; CELL FATE; CELL TOTIPOTENCY; CELL WALL; DIFFERENTIATION; EPIGENETIC MARKS; MICROSPORE EMBRYOGENESIS; PHYTOHORMONES; STRESS